The results of the immunological studies using modern technology in the treatment of chronic apical periodontitis (Эндодонтия Today)
The work is devoted to the evaluation of the effectiveness of apex-phoresis in the treatment of chronic apical periodontitis. The influence of apex-phoresis on the immune response periodontal segment is studied, terms of bone regeneration in areas of destruction are defined. As a result of immunological research it was found that the efficiency of the method of apex-phoresis was implemented in the redistribution of the structure of immune cells, increase in the number of neutrophils and lymphocytes. The increased phagocytosis activity, functional activity of neutrophils and erythrocytes was observed. The proposed method can reduce the quantity of complications and adverse outcomes, increase the percentage of positive results and shorten the time of treatment.